AB0326 Matrix metalloproteinase-3 is a good predictor for joint destruction only in male patients with rheumatoid arthritis. (12th June 2018) - Yamada, Y.; Inui, K.; Okano, T.; Orita, K.; Sugioka, Y.; Mamoto, K.; Koike, T.; Tada, M.; Nakamura, H.
Abstract : Background: Serum level of matrix metalloproteinase-3 (MMP-3) is elevated by synovial inflammation. It destroys articular cartilage such as proteoglycans so that it has been used as a clinical biomarker of joint destruction in patients with rheumatoid arthritis (RA). Objectives: The purpose of this study is to investigate a relation between radiographic progression, MMP-3 and other factors such as ultrasonography (US) findings. Methods: 259 patients (213 women) with RA were enrolled in this study. Their baseline data such as age, sex, disease duration, use of glucocorticoid (GC) or DMARDs, disease activity (DAS28), laboratory data (MMP-3, CRP, RF and ACPA), and the Power Doppler (PD) score at digits and wrists by US were collected. The modified total Sharp score (mTSS), erosion score (ERN) and joint space narrowing (JSN) were examined at baseline and 1 year. Their changes from baseline to 1 year (Δ) were calculated. Relationship between baseline MMP-3 and other variables was examined. Predictors for joint destruction was investigated by multiple regression. Statistical analysis was separated by sex because upper limit of MMP-3 is different between men and women. Results: MMP-3 showed no correlations with GC use, DAS28, CRP or mTSS. MMP-3 was correlated with ΔmTSS and ΔJSN only in men, but PD score only in women (table 1). Multiple regression analysis revealed that MMP-3 was correlated independently with ΔmTSS only in men, whereas PD score was correlated independently with ΔmTSS in women. PD score, but not MMP-3, could predict joint destruction at 1 year in women (table 2). Conclusions: The baseline MMP-3 was a good predictor for joint destruction at 1 year only in male patients with RA. On the other hand, the baseline PD score was a useful predictor for joint destruction only in female patients with RA. Disclosure of Interest: None declared